Studi Kristologi Berdasarkan Mazmur 110 - Ryan Renaldy Madunde (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
AbstractThe doctrine of Christology is a central doctrine in the Christian faith, the belief in His divine and human nature is a doctrine that can no longer be negotiated. And from the time of the Apostles, the Apostolic Fathers, the Church Fathers to this day the whole church agrees and there is no difference as to this confession of faith. But the teaching of the double quadrant of Jesus Christ is not as easy to say, in the course of history it has proved to be a serious debate that needs to be given extra attention by every church of God today in its study. Added to the question of how as evangelical theologians can prove whether the Old Testament prophesied the person of Jesus and was truly fulfilled in Him, as in Psalm 110: 1-7, how the psalmist reveals the person of Jesus in his writings while the Psalms have a poetic genre where the background of the writing was not disclosed. That is why the study of Christianity based on Psalm 110: 1-7 needs to be done carefully to establish a correct and responsible Doctrine of Critology.Keywords: Jesus, Doctrine of Christology, Book of Psalms